2014
DOI: 10.1111/ajo.12270
|View full text |Cite
|
Sign up to set email alerts
|

Incisional hernia repair after caesarean section: a population‐based study

Abstract: word count: 250 Abstract BACKGROUND

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…1. A total of five studies were included in this systematic review [17][18][19][20][21]. No additional studies were included from the snowball search.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1. A total of five studies were included in this systematic review [17][18][19][20][21]. No additional studies were included from the snowball search.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 275,878 women with a previous cesarean section were included, resulting in 286,585 cesarean sections in total. Of the 286,585 cesarean sections 217,155 (76 %) originated from one of the included studies [17]. One study reported all midline incisions [19] and two reported above 50 % midline incisions [20,21].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rate of patients who need incisional hernia repair after a cesarean section was reported to be 0.47% [1]. Surgical meshes are widely used in incisional hernia repair.…”
Section: Introductionmentioning
confidence: 99%